MODERN REQUIREMENTS TO THE GENERAL EDUCATIONAL ESTABLISHMENTS LEADERS IN FOREIGN COUNTRIES (FOREIGN EXPERIENCE) - Malitskaya, І.Д. (Journal of Information Technologies in Education (ITE), 2010)
As a result of ICT integration into the school educational and administrative process, ICT competence is being included in normative educational documents and standards. In the article it has been considered modern requirements to the school leaders in foreign countries (The USA, Lithuania, European countries), it is presented the National educational technological standards (NETS•A). Performance indicators for administrators developed by International society for technology in education ISTE, which is used for development of their own standards in different foreign countries.